Furniture Design as a Sensory Product Approach in Autism Therapy for Children - Ishak, Nur Dinie Aliah; Toyong, Natrina; Romli, Zulkifli; Purnamasari, Ni Putu Laras (Environment-Behaviour Proceedings Journal, 2023)
Autism Spectrum Problem (ASD) is a childhood communication and behavioral disorder. Even though ASD is a lifelong condition, medications and therapies can help autistic children with their symptoms and abilities to function. The research uncovers the viability of furniture design solution as an alternative sensory product that considers autistic children’s outbursts as it relates to their surrounding and environment. The purpose of the study is to discover how sensory products can assist autistic children by analyzing the Three Levels of Design prescribed by Don Norman, focusing on the Visceral, Behavioral and Reflective elements that apply to the furniture design domain.